Empagliflozin Effects on Pulmonary Artery Pressure in Patients With Heart Failure: Results From the EMBRACE-HF Trial. Issue 17 (27th April 2021) - Nassif, Michael E.; Qintar, Mohammed; Windsor, Sheryl L.; Jermyn, Rita; Shavelle, David M.; Tang, Fengming; Lamba, Sumant; Bhatt, Kunjan; Brush, John; Civitello, Andrew; Gordon, Robert; Jonsson, Orvar; et al.
Abstract : Background: Sodium glucose cotransporter 2 inhibitors (SGLT2 inhibitors) prevent heart failure (HF) hospitalizations in patients with type 2 diabetes and improve outcomes in those with HF and reduced ejection fraction, regardless of type 2 diabetes. Mechanisms of HF benefits remain unclear, and the effects of SGLT2 inhibitor on hemodynamics (filling pressures) are not known. The EMBRACE-HF trial (Empagliflozin Evaluation by Measuring Impact on Hemodynamics in Patients With Heart Failure) was designed to address this knowledge gap. Methods: EMBRACE-HF is an investigator-initiated, randomized, multicenter, double-blind, placebo-controlled trial. From July 2017 to November 2019, patients with HF (regardless of ejection fraction, with or without type 2 diabetes) and previously implanted pulmonary artery (PA) pressure sensor (CardioMEMS) were randomized across 10 US centers to empagliflozin 10 mg daily or placebo and treated for 12 weeks. The primary end point was change in PA diastolic pressure (PADP) from baseline to end of treatment (average PADP weeks 8–12). Secondary end points included health status (Kansas City Cardiomyopathy Questionnaire score), natriuretic peptides, and 6-min walking distance. Results: Overall, 93 patients were screened, and 65 were randomized (33 to empagliflozin, 32 to placebo). The mean age was 66 years; 63% were male; 52% had type 2 diabetes; 54% were in New York Heart Association class III/IV; mean ejection fraction was 44%; median NT-proBNP (N-terminal pro B-type natriuretic peptide) was 637 pg/mL; and mean PADP was 22 mm Hg. Empagliflozin significantly reduced PADP, with effects that began at week 1 and amplified over time; average PADP (weeks 8–12) was 1.5 mm Hg lower (95% CI, 0.2–2.8; P =0.02); and at week 12, PADP was 1.7 mm Hg lower (95% CI, 0.3–3.2; P =0.02) with empagliflozin versus placebo. Results were consistent for PA systolic and PA mean pressures. There was no difference in mean loop diuretic management (daily furosemide equivalents) between treatment groups. No significant differences between treatment groups were observed in Kansas City Cardiomyopathy Questionnaire scores, natriuretic peptide levels, and 6-min walking distance. Conclusions: In patients with HF and CardioMEMS PA pressure sensor, empagliflozin produced rapid reductions in PA pressures that were amplified over time and appeared to be independent of loop diuretic management. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT03030222. Abstract : Supplemental Digital Content is available in the text.